Analysis of the use of isometric exercises to prevent injuries in beach soccer players - Brynzak, S.; Putrov, S.; Olena, O.; Kostenko, M.; Shnichenko, V. M. (Journal of Physical Education and Sport, 2023)
The article is devoted to the problem of using isometric exercises to prevent injuries in beach soccer players. The purpose of the work was to substantiate the effectiveness of the methodology of using a set of isometric exercises to avoid damage to beach soccer players in the sports training system. The following research methods were used: theoretical analysis and generalization of literature sources; pedagogical observation; pedagogical experiment (stating, forming); methods of mathematical statistics. The current stage of formation and popularization of beach soccer in Ukraine and the world is characterized by a significant increase in training and competitive loads, which in turn requires the prevention of injuries to players. The generally accepted methods of solving this issue only sometimes give the desired result due to the peculiarities and specifics of this sport. The study included the study of scientific, theoretical, and methodological aspects of the problem, conducting a survey of qualified players, coaches, and medical staff of men's teams, determining the level of physical fitness of beach soccer players, selection of isometric exercise complexes to prevent injuries to players, experimental substantiation of the methodology of using isometric exercise complexes in the training process of beach soccer. The analysis of scientific and methodological literature and survey of respondents allowed us to identify common types and leading causes of injuries of beach soccer players. It was found that isometric exercises are significant (p<0.05) for increasing physical fitness and preventing injuries in beach soccer players. The obtained data allowed us to substantiate the methodology of using isometric exercises in the annual training cycle, which showed effectiveness in preventing injuries in the training of beach soccer players.